Rubber composites based on silane-treated stöber silica and nitrile rubber: Interaction of treated silica with rubber matrix. (April 2015) - Kapgate, Bharat P; Das, Chayan; Basu, Debdipta; Das, Amit; Heinrich, Gert
Role of silane-treated stöber silica as reinforcing filler for nitrile rubber (NBR) has been studied. Stöber silica is synthesized by sol–gel method, and the surface of silica is modified with the treatment of silane-coupling agent viz. γ-mercaptopropyltrimethoxysilane (γ-MPS) in varying proportions. Average particle size of stöber silica of spherical shape in the range of 200 to 400 nm is evident from scanning electron microscopy (SEM). Surface modification of silica particle with silane-coupling agents decreases surface energy and reduces agglomeration of silica particles in rubber matrix. Stress–strain study and dynamic mechanical analysis of silica-filled composites are compared with the unfilled ones. Analysis of cross-linking density, mechanical properties, and storage moduli indicates a strong rubber–filler interaction in the silane-treated, silica-filled NBR composites. Silane treatment is found to be effective in uniform dispersion of silica in rubber matrix and in improving the mechanical properties of rubber composite. Different functionalities of organosilane at its both end improve the compatibility of silica with rubber matrix and offer better rubber–filler interaction.